Reserve Requirements, Liquidity Risk, and Credit Growth - Koray Alper; Mahir Binici; Selva Demiralp; Hakan Kara; Pınara Özlü (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Many central banks in emerging economies have used reserve requirements (RR) to alleviate the trade-off between financial stability and price stability in recent years. Notwithstanding their widespread use, transmission channels of RR have remained largely as a black-box. In this paper, we use bank-level data to explore the interaction between RR and bank lending behavior. Our empirical findings suggest that short-term borrowing from the central bank is not a close substitute for deposits for banks. Bank lending behavior responds significantly to reserve requirements and liquidity positions. Our analysis allows us to identify a new channel that we name as the "liquidity channel". The channel works through a decline in bank liquidity and loan supply due to an increase in reserve requirements.
Keywords: E44; E51; E52; 330; Monetary transmission mechanism; liquidity risk; bank lending channel; Turkey